Epidemiological Profile of Violence against the Elderly in the State of Minas Gerais, Brazil - Gabriela Fernandes de Oliveira; Breno Resende Rodrigues da Cunha; Anderson de Cintra Souza; Mariana Giorgiani; Juliana Rizza Ribeiro Batista; Paula Monikee Rezende Alves; Maria Tereza Néri Rosa; Stefan Vilges de Oliveira (Ital Publication, 2019)
Purpose: The main objective of the present study is to evaluate the violence against the elderly population of the Minas Gerais state, between 2007 and 2017, in order to draw an epidemiologic profile of these events through the gathering of secondary data registered by the Information System for Notifiable Diseases (SINAN). Methods: We analyzed data from the public health system between 2007 and 2017, in order to draw an epidemiologic profile of these events through the gathering of secondary data registered by the Information System for Notifiable Diseases (SINAN). The acts of violence committed were classified according to the injured body part, the number of people involved, the sex of the victim, suspect of alcohol abuse by the aggressor, the race, the marital status, the location, the aggressor's gender, the relationship with the victim and the evolution to death. Results: By analyzing this data, it was possible to notice 15086 notifications of violence against the elderly in 814 cities of the Minas Gerais state, and 122 of those cities had cases that resulted in deaths.  Conclusion: Hence, it was possible to conclude that several aspects exist in this kind of violence, such as the victim's gender, the type of violence, the number of aggressors, relationship, and others still. Thereby, this study highlights the need of more research on this topic, in order to offer better combat against this type of violent actions, since the increase of the elderly population is due to Brazil's demographic transition that has been occurring in the last years.